PENGARUH KUALITAS PRODUK DAN DAYA TARIK IKLAN TERHADAP MINAT BELI VASELINE HEALTHY WHITE INSTA FAIR - FICHA MEGA RAHMANIA, ADINDA (Jurnal Pendidikan Tata Niaga (JPTN), 2015)
Development efforts have now characterized by a wide variety of competition in every aspects, especially in the aspects beauty is cosmetic products which one of them is a body lotion. Vaseline Healthy White Insta Fair that functioning to brighten skin instantly from the first applied. However, Vaseline Healthy White Insta Fair not forgotten the element of advertising that shows the benefit and advantages. The population of this study is consumers who have used the product Vaseline in addition to the variant Vaseline Healthy White Insta Fair. The sample in this study amounted to 104 with accidental and purposive technique sampling. Data collection techniques with questionnaire. The results showed that product quality and attractiveness of advertising influence on buying interest is 54,0%. Partially, the variable quality product is more dominant influence on buying interest is 7,288 while the variable attractiveness of advertising influence on buying interest is 2,868. Keyword: quality products, advertising attractions and purchase interest.